Observed hand cleanliness and other measures of handwashing behavior in rural Bangladesh - Halder Amal K; Tronchet Carole; Akhter Shamima; Bhuiya Abbas; Johnston Richard; Luby Stephen P (BMC, 2010)
Abstract Background We analyzed data from the baseline assessment of a large intervention project to describe typical handwashing practices in rural Bangladesh, and compare measures of hand cleanliness with household characteristics. Methods We randomly selected 100 villages from 36 districts in rural Bangladesh. Field workers identified 17 eligible households per village using systematic sampling. Field workers conducted 5-hour structured observations in 1000 households, and a cross-sectional assessment in 1692 households that included spot checks, an evaluation of hand cleanliness and a request that residents demonstrate their usual handwashing practices after defecation. Results Although 47% of caregivers reported and 51% demonstrated washing both hands with soap after defecation, in structured observation, only 33% of caregivers and 14% of all persons observed washed both hands with soap after defecation. Less than 1% used soap and water for handwashing before eating and/or feeding a child. More commonly people washed their hands only with water, 23% after defecation and 5% before eating. Spot checks during the cross sectional survey classified 930 caregivers (55%) and 453 children (28%) as having clean appearing hands. In multivariate analysis economic status and water available at handwashing locations were significantly associated with hand cleanliness among both caregivers and children. Conclusions A minority of rural Bangladeshi residents washed both hands with soap at key handwashing times, though rinsing hands with only water was more common. To realize the health benefits of handwashing, efforts to improve handwashing in these communities should target adding soap to current hand rinsing practices.